2021
DOI: 10.1101/gad.348667.121
|View full text |Cite
|
Sign up to set email alerts
|

Role of 53BP1 in end protection and DNA synthesis at DNA breaks

Abstract: Double-strand break (DSB) repair choice is greatly influenced by the initial processing of DNA ends. 53BP1 limits the formation of recombinogenic single-strand DNA (ssDNA) in BRCA1-deficient cells, leading to defects in homologous recombination (HR). However, the exact mechanisms by which 53BP1 inhibits DSB resection remain unclear. Previous studies have identified two potential pathways: protection against DNA2/EXO1 exonucleases presumably through the Shieldin (SHLD) complex binding to ssDNA, and localized DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 51 publications
(95 reference statements)
1
27
1
Order By: Relevance
“…17 ). This spectrum of byproducts is dissimilar to the ∼1-5bp indels typically observed with Cas9 nucleases and has been previously reported 59 . In fact, most clones (55/58) that were not homozygous for the PE3-specified MTOR mutations contained undesired insertions, deletions or pegRNA scaffold incorporations ( Table 1 and Supplementary Figs.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…17 ). This spectrum of byproducts is dissimilar to the ∼1-5bp indels typically observed with Cas9 nucleases and has been previously reported 59 . In fact, most clones (55/58) that were not homozygous for the PE3-specified MTOR mutations contained undesired insertions, deletions or pegRNA scaffold incorporations ( Table 1 and Supplementary Figs.…”
Section: Resultscontrasting
confidence: 75%
“…These editing byproducts are reminiscent to the DSB repair response resulting from presence of concomitant nicks 56 . Mechanistically, fill-in synthesis of the 3' protruding ends generated by concomitant nicks via Polα-primase could account for these tandem duplications in a pathway that requires 53BP1 [57][58][59] . We thus tested whether the inhibition of 53BP1 with i53 60 could prevent the formation of large PE3-mediated insertions by delaying rapid and predominant NHEJ-mediated repair.…”
Section: )mentioning
confidence: 99%
“…In mammalian cells, it has been suggested that unrestricted resection may not be the only model for the increased ssDNA in the absence of 53BP1, rather it could also be due to impaired gap filling 9, 37 . Recent work has shown that 53BP1 facilitates gap filling by recruitment of Shieldin and subsequently the CST complex and Pol- alpha primase 38, 39 . However, there may be differences between the functions of Rad9 and 53BP1 as our data shows that gap filling occurs without delay in the absence of Rad9 and any role Rad9 may have in recruitment of gap filling factors is not essential for completion of fill-in synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…CST facilitates RAD51 recruitment to forks, whereas RPA-coated ssDNA inhibits RAD51 nuclear filament formation [18]. During DSB repair, CST appears to promote c-NHEJ via inhibiting excessive end resection through a POLα-dependent fill-in mechanism [26,27,47], whereas RPA stimulates end resection and promotes homologous recombination [28][29][30]. The structural difference between CST and RPA may help in explaining distinct functionalities of these two ssDNA-binding complexes in various genome maintenance pathways.…”
Section: Discussionmentioning
confidence: 99%